Formation of the architecture of Ukraine based on longstanding measurement standards - Olena Khramova-Baranova (Історія науки і техніки, 2020)
The article, on the basis of a fundamental study of literature and its thorough analysis, highlights the importance of measurements in the cultural aspect of the development of the country and types of art. The analysis of literary sources is carried out, which confirms the influence of the formation of measurement standards on the development of the main types of art. The relevance of the topic is to show the connection between the development of technical thought and the formation of art forms, which has become one of the foundations of the general development of the culture of the state. I. Babenko, M. Bieliaiev, D. Mendelieiev, E. Kamentseva, B. Rybakov and others made a great contribution to the formation and development of measurement standards that influenced the cultural development of the state. In their fundamental works one can find information on the influence of measurement on formation and development of architecture, arts and crafts. But these materials do not give a complete picture of the conceptual significance of the influence of technical thought on art and the cultural development of the state. The purpose of the article is to show the influence of the technical thought development, namely the metrological foundations, on the development of the arts. The centuries-old history of metrology is useful for the development of society, although its origin and development are covered only in scattered sources. One of the fundamental studies of the origin of measures was the works of I. Babenko “Metrology”, M. Bieliaiev “On ancient and modern Russian measures of extension and weight”, and B. Rybakov in his writings presented fathoms as geometric lines of the calculation table of architects (Babylon). The history of measurements is highlighted in the literature and is mainly devoted to the processes on the formation of metrological concepts among the Skifiia, Sarmatiia, the Zarubinets and Cherniakhiv cultures, the Northern Prychornomoria, of Kyivska Rus, Moskoviia and other. Neither in the ancient world, nor in the Middle Ages there was a metrological service, but there is information about the implementation of standards and storage of measures, as well as about the verification of measuring instruments. Accurate measurements and calculations allowed the architect to achieve harmony in the creation of architectural monuments.